Inadequate Bowel Preparation in Pediatric Colonoscopy—Prospective Study of Potential Causes. Issue 3 (September 2021) - Kumar, Sanjay; Bennett, William E.; Bozic, Molly A.; Croffie, Joseph M.; Ferrell, Emily; Hon, Emily C.; Khan, Hamza H.; McFerron, Brian A.; Molleston, Jean P.; Pfefferkorn, Marian D.; Steiner, Steven J.; Rao, Girish S.; et al.
ABSTRACT: Objectives: Inadequate bowel preparation (IBP) for colonoscopy leads to missed diagnosis, longer anesthesia time, higher chance of complications and increased costs. Adult studies have demonstrated that patient characteristics such as male gender and obesity are associated with IBP. Little is known about factors affecting bowel preparation in children. Our aim was to determine factors associated with IBP in children. Methods: We prospectively enrolled children undergoing outpatient colonoscopy. Quality of bowel preparation was assessed using Boston Bowel Preparation Scale (BBPS) score (range 0–9). Data collected included patient demographics, indication, and type of insurance. Patients were divided into two groups based on BBPS score—adequate (BBPS score > 5) and inadequate (BBPS score < 5) and groups were compared using Student t -test and chi-square test. Possible predictors were analyzed using multivariate logistic regression models. Results: A total of 334 children were prospectively enrolled of whom 321 were studied further (age range 2–18 years; mean age 12.4 years; 60.4% female; 85.9% Caucasian). The mean BBPS score was 6.8 (standard deviation of ±2). IBP was reported in 12.8% (41/321). Multivariable logistic regression analysis did not show statistical differences between the groups in studied patient factors including age, gender, obesity, race, insurance type, and indication for colonoscopy. Conclusion: Contrary to several adult studies, the results of our prospective study did not show any relationship between examined patient factors and IBP in children. Interestingly, IBP was less prevalent in our pediatric study compared to published adult data (12.8% vs 20–40%). Abstract : Supplemental Digital Content is available in the text